Determining Adequacy. Supplementary Paper to the Final Report of the Pensions Working Group (Central Bank of Malta, 2005)
This paper attempts to define 'adequate' in order to guide the Pensions Working Group in the determination of an adequate replacement rate within a sustainable pensions system. The definition for adequacy applied is that presented by the Watts Committee in the United States in 1980: "Adequacy affords full opportunity to participate in contemporary society and the basic options it offers." The needs of pensioner types presented in this Report represent hypothetical and not actual households. It is pertinent to underline that few households have identical needs and preferences. For example some older households manage happily without a car, for others, car ownership is a necessity. (...)
Keywords: 330